A tribute to Nilabh Shastri and a special issue on antigen processing and presentation in Paris (APP10, Paris 2019). (May 2022) - Hosmalin, Anne; Manoury, Bénédicte
Abstract: The Special Issue is dedicated to the 10th Antigen Processing and Presentation Workshop, which took place at Institut Cochin in Paris from May 28th to June 2nd, 2019. It contains several reviews or original articles from contributors to this workshop. It is also a vibrant Tribute to Nilabh Shastri, founder of the APP Workshops, who untimely passed away in 2021 and is deeply missed by his colleagues and friends. Highlights: The Special Issue is dedicated to the 10th Antigen Processing and Presentation Workshop, Institute Cochin, Paris 2019. It contains several reviews or original articles from contributors to this workshop. It is also a vibrant Tribute to Nilabh Shastri. Nilabh Shastri, co-founder of the APP Workshops, untimely passed away in 2021 and is deeply missed bycolleagues and friends.